Reinforced concrete design - Wang, Chu-Kia. (Addison-Wesley, 1998)
This book contains: Design methods and requirements; Strength of Rectangular Sections in Bending; Rectangular Sections in Bending Under Service Load Conditions; Shear Stregth and Shear Reinforcement; Development of Reinforcement...